2014
DOI: 10.1007/978-3-319-11863-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Code Pitfalls in Aspect-Oriented Programming

Abstract: Abstract. Aspect-Oriented Programming (AOP) is a maturing technique that requires a good comprehension of which types of mistakes programmers make during the development of applications. Unfortunately, the lack of such knowledge seems to represent one of the reasons for the cautious adoption of AOP in real software development projects. Based on a series of experiments, this paper reports a catalogue of code pitfalls that are likely to lead programmers to make mistakes in AOP. Each experiment required the aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Reuse (Long, 2001) Architecture (Garcia et al, 2009), Design (Suryanarayanaet al, 2014, Aspect-Oriented (Alves et al, 2014) Table 1 summarizes the accumulation of 14 categories identified by (Sharma and Spinellis, 2018) into the 7 consolidated ones. Considering the space constraints of the article, the description about the chosen categories can be understood using respective references.…”
Section: IIImentioning
confidence: 99%
“…Reuse (Long, 2001) Architecture (Garcia et al, 2009), Design (Suryanarayanaet al, 2014, Aspect-Oriented (Alves et al, 2014) Table 1 summarizes the accumulation of 14 categories identified by (Sharma and Spinellis, 2018) into the 7 consolidated ones. Considering the space constraints of the article, the description about the chosen categories can be understood using respective references.…”
Section: IIImentioning
confidence: 99%
“…As discussed in section 'Introduction', AOP is typically applied to refactor existing systems to achieve better modularisation of crosscutting concerns [2,[33][34][35][36]. Given this scenario of AOP adoption, our recent work investigated the difficulty of testing AO and OO programs, in particular when there is a migration from one paradigm to the other.…”
Section: Reuse-centred Viewpoint Analysismentioning
confidence: 99%
“…From our experience and observations, when adopted, AOP is applied to refactor existing objectoriented (OO) systems to achieve better modularisation of behaviour that appears intertwined or spread across the system modules (these are the so-called crosscutting concerns [32]). Examples of AOP applied in this context can be found in the work of van Deursen et al [2], Mortensen et al [33], Ferrari et al [34] and Alves et al [35,36], not limited to particular technologies such as Java and AspectJ.…”
Section: Introductionmentioning
confidence: 99%